Deposition of elafin in the involved vascular wall of neutrophil‐mediated cutaneous vasculitis. (6th April 2016) - Muto, J.; Fujimoto, N.; Ono, K.; Kobayashi, T.; Chen, K.R.; Suzuki, S.; Wachi, H.; Tajima, S.
Abstract: Background: Neutrophil elastase plays an important role in skin inflammation induced by neutrophil infiltration. Elafin is an inducible elastase inhibitor expressed by keratinocytes, and is known to be involved in pathogenesis of neutrophilic skin disorders such as psoriasis. Methods: Immunohistochemical studies of elafin expression in the cases of vasculitis were performed. Induction of elafin expression in cultured vascular cells and its effect on neutrophil migration were studied in vitro . Results: A positive immunoreactivity was detected in polyarteritis nodosa, giant cell arteritis and Schönlein–Henoch purpura, but no immunoreactivity was found in Churg–Strauss syndrome. Elafin expression in cultured venous endothelial cells and arterial smooth muscle cells was undetectable, but induced by interleukin‐1β (IL‐1β) and IL‐8. Elafin inhibited the elastin peptide‐induced neutrophil chemotaxis at the concentration of 10 −8 –10 −5 mol/L. Conclusion: Elafin deposition induced by cytokines (IL‐1β or IL‐8) will be an important regulator for the progress of leucocytoclastic vasculitis by functioning as an inhibitor for neutrophil chemotaxis as well as for vascular elastin degradation.